Solve for f 5/9*(f-32)=-62.1

Math
59⋅(f-32)=-62.1
Multiply both sides of the equation by 95.
95⋅59⋅(f-32)=95⋅-62.1
Simplify both sides of the equation.
Tap for more steps…
Simplify 95⋅59⋅(f-32).
Tap for more steps…
Cancel the common factor of 9.
Tap for more steps…
Cancel the common factor.
95⋅59⋅(f-32)=95⋅-62.1
Rewrite the expression.
15⋅5⋅(f-32)=95⋅-62.1
15⋅5⋅(f-32)=95⋅-62.1
Cancel the common factor of 5.
Tap for more steps…
Cancel the common factor.
15⋅5⋅(f-32)=95⋅-62.1
Rewrite the expression.
1⋅(f-32)=95⋅-62.1
1⋅(f-32)=95⋅-62.1
Multiply f-32 by 1.
f-32=95⋅-62.1
f-32=95⋅-62.1
Simplify 95⋅-62.1.
Tap for more steps…
Multiply 95⋅-62.1.
Tap for more steps…
Combine 95 and -62.1.
f-32=9⋅-62.15
Multiply 9 by -62.1.
f-32=-558.95
f-32=-558.95
Divide -558.9 by 5.
f-32=-111.78
f-32=-111.78
f-32=-111.78
Move all terms not containing f to the right side of the equation.
Tap for more steps…
Add 32 to both sides of the equation.
f=-111.78+32
Add -111.78 and 32.
f=-79.78
f=-79.78
Solve for f 5/9*(f-32)=-62.1

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top